Soy and legume seeds as sources of isoflavones: selected individual determinants of their consumption in a group of perimenopausal women - Gacek, Maria (Menopause Review/Przegląd Menopauzalny, 2014)
The aim of this study was to analyze selected individual determinants of consumption of soy products and legumes by menopausal women. The analyzed individual characteristics included the level of general self-efficacy, optimism, and satisfaction with life. The study, using a questionnaire for the assessment of food product consumption frequency, and psychological tests (GSES, LOT-R, SWLS), was conducted in a group of 320 women aged between 45 and 55 years. Spearman’s coefficient of rank correlation and the Kruskal-Wallis test with the Dunn test for multiple comparisons were used for statistical analysis (p < 0.05). Material and methods: The analyzed 45-55-year-old women consumed legume seeds several times a month on average, while the frequency of soy/soy product consumption was lower than once a month. Statistical analysis revealed that the frequency of soy product consumption increased with the level of self-efficacy, optimism and satisfaction with life (p < 0.01). Also the increased frequency of legume seed consumption was associated with higher level of optimism and satisfaction with life (p < 0.01). Results: Intergroup comparisons of the average consumption frequency of these products confirmed that legume seeds were significantly more frequently chosen by women characterized by high rather than low levels of optimism (3.36 vs. 2.62, p < 0.001) and satisfaction with life (3.36 vs. 2.65, p < 0.01). Also soy products were preferred significantly more often by women with higher levels of optimism (2.00 vs. 1.38, p < 0.05) and satisfaction with life (2.02 vs. 1.39, p < 0.05). Conclusions : The consumption of legume seeds, and especially soy products, was revealed to be very low among perimenopausal women, and varied depending on the analyzed individual traits, with a tendency to more frequent ingestion by individuals with higher levels of self-efficacy, optimism, and satisfaction with life.